Predictors of new vertebral endplate signal (Modic) changes in the general population - Jensen, Tue Secher (Springer-Verlag, 2009)
Vertebral endplate signal changes (VESC), also known as Modic changes, have been reported to be associated with low back pain (LBP). However, little is known about predisposing factors for the development of new VESC. The aim of this study was to investigate the predictive value of lifestyle factors and disc-related magnetic resonance imaging (MRI) findings in relation to the development of new VESC. This prospective observational study included 344 people from the Danish general population who had an MRI and completed LBP questionnaires at the age of 40 and again at 44 years. Potential predictors of new VESC were female gender, disc-related MRI findings (disc degeneration, disc bulges, disc herniation, and other endplate changes) and lifestyle factors [high physical work or leisure activity, high body mass index (BMI), and heavy smoking]. Bivariate and multivariate logistic regressions were used to identify predictors of new VESC. New VESC at the age of 44 appeared in 67 of the 344. The majority (84%) of these new signal changes were type 1 VESC and almost half (45%) were only in the endplate and did not extend into the vertebral body. In the multivariate analysis, lumbar disc levels with disc degeneration, bulges or herniations at 40 were the only predictors of new VESC at age 44. Therefore, the development of new VESC at the age of 44 appears to be based on the status and dynamics of the disc, rather than being the result of gender or lifestyle factors such as smoking and physical load.